The New Family Arrangements as Overcoming Traditionalism: Pluralism and the Concretization of Fundamental Rights in Brazil - Marcos Augusto Maliska; Marilaine Moreira de Jesus (As-Siyasi, 2023)
Traditionalism is an ideology that advocates for a government founded on principles surpassing mere human and individual aspects. In traditional symbolism, the supernatural principle is invariably regarded as masculine, and that of nature as feminine. Traditionalism underscores the necessity for the family entity to acknowledge the metaphysical dyad distinguishing the masculine from the feminine, contending that the sole legitimate family form is that constituted by the union of a man and a woman and their offspring. This paper seeks to examine the shift from traditionalism to constitutional pluralism within the realm of family entities. It aims to comprehend how constitutional pluralism acknowledges the diversity of family forms and facilitates societal changes in the concept of the family, all the while circumventing state censorship and bolstering individual liberty. The approach utilised is one of normatibrave juridical enquiry. The study reveals that new family structures, rooted in constitutional pluralism, foster the displacement of traditionalism, thereby establishing a new paradigm for interpreting the concept of the family as defined by the Constitution. Traditionalism, having historically occupied a dominant stance regarding the family, yields to pluralism. The realisation of fundamental rights ensures the diversity of family entities, inclusive of the traditional family's rightful claim to existence. Viewed from the vantage point of a pluralistic family constitutional framework, traditionalism should not be perceived as antagonistic to pluralism but rather as one of its valid manifestations a legitimate approach to experiencing life and perceiving the world.